D5.1 Leaflets - Tzouvaras, Marios; Agapiou, Athos; Christofe, Andreas; Lysandrou, Vasiliki; Nisantzi, Argyro; Mettas, Christodoulos; Evagorou, Evagoras G.; Papoutsa, Christiana; Themistocleous, Kyriacos; Neocleous, Kyriacos; Hadjimitsis, Diofantos G.; Lasaponara, Rosa; et al. (My University, 2018)
The specific deliverable is a collection of the special leaflets that were designed to inform stakeholders and other possible interested parties regarding the activities of the Remote Sensing lab within the framework of ATHENA project. For this purpose, 14 special leaflets were designed and uploaded on the project’s website. Additional information will be provided to all interested parties via the WP6 deliverables of the project.
Keywords: ATHENA project; Leaflets